Transient dynamic analysis of bars and trusses by the adaptive generalized finite element method. Issue 3 (23rd August 2019) - Col Debella, Leticia; Cittadin, Carolina Castro; Arndt, Marcos; Machado, Roberto Dalledone
Abstract : Purpose: This paper aims to present an adaptive approach of the generalized finite element method (GFEM) for transient dynamic analysis of bars and trusses. The adaptive GFEM, previously proposed for free vibration analysis, is used with the modal superposition method to obtain precise time-history responses. Design/methodology/approach: The adaptive GFEM is applied to the transient analysis of bars and trusses. To increase the precision of the results and computational efficiency, the modal matrix is responsible for the decoupling of the dynamic equilibrium equations in the modal superposition method, which is used with only the presence of the problem's most preponderant modes of vibration. These modes of vibration are identified by a proposed coefficient capable of indicating the influence of each mode on the transient response. Findings: The proposed approach leads to more accurate results of displacement, velocity and acceleration when compared to the traditional finite element method. Originality/value: In this paper, the application of the adaptive GFEM to the transient analysis of bars and trusses is presented for the first time. A methodology of identification of the preponderant modes to be retained in the modal matrix is proposed to improve the quality of the solution. The examples showed that the method has a strong potential to solve dynamic analysis problems, as the approach had already proved to be efficient in the modal analysis of different framed structures. A simple way to perform h -refinement of truss elements to obtain reference solutions for dynamic problems is also proposed.